EFEKTIFITAS PIJAT MARMET UNTUK MELANCARKAN AIR SUSU IBU DI PRAKTEK MANDIRI BIDAN ETRAWATI TAHUN 2022 - Lasria Simamora; Etrawati Etrawati; Dewi Sari Br.Pasaribu; Padhilah Pasmi; Maria Siahaan; Henni Rista (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Background: Mother's milk is a natural food that is good for babies because breast milk has many advantages containing important substances that make babies develop optimally. Along with the development of medical science, experts find ways to increase milk production, namely pharmacological and non-pharmacological methods. One of the non-pharmacological methods is the marmet technique. Marmet technique is a technique used to express breast milk. This technique provides a relaxing effect and also reactivates the milk ejection reflex (MER) so that the milk begins to drip. With the activation of MER, the milk will often spray out by itself. The purpose of this activity is to increase knowledge and understanding of the benefits of the marmet technique on the smooth flow of breast milk. Methods: service is carried out using counseling methods, demonstrations and observations of the marmet technique. Results: from education conducted on 20 postpartum mothers, it was found that there was an increase in knowledge of postpartum mothers from poor knowledge to good and 20 postpartum mothers experienced an increase in breast milk expenditure from 20 postpartum mothers experienced an increase in milk production by 18 people (90%).